A study on the effectiveness of display at ladies department, Jaya Jusco Bandar Baru, Klang / Mahani Mohamad - Mohamad, Mahani (1997)
Consumer shopping behaviour such as the choice of store is influenced based on how merchandising of a firm's positioning strategy. Merchandise display is an important ingredient creating element where should begin with an understanding of preferences, desires and expectations of the target market. Merchandise display effectively can be used to excite, entertain and educate customers. It also can be called silent language of communication where it can have a profound influence on consumer behaviour. Retailers must use store display as a competitive weapon, appealing to the changing lifestyles of their target shoppers. Within the store consumers not only respond to the products being offered but also to their surrounding. The creative use of display will affect shoppers desire to shop and the amount of time spent in the store. Merchandise presentation is important aspect where the major goal is to get the shoppers into the store to spend as much money as possible on a given shopping trip. The report is been written to study the important of Ladies department display and the effectiveness of it. It also discuss the customer perception towards merchandise presentation at the department that lead to customer satisfaction.